Composition and antimicrobial activity of hydroalcoholic extracts of Pleurotus eryngii var. ferulae and P. eryngii var. elaeoselini - Flavio Polito; Laura De Martino; Giulia Mirabile; Giuseppe Venturella; Maria Letizia Gargano; Vincenzo De Feo; Hazem S. Elshafie; Ippolito Camele (Frontiers in Chemistry)
BackgroundThe basidiomycetes Pleurotus eryngii var. ferulae Lanzi and P. eryngii var. elaeoselini Venturella et al. belong to the P. eryngii species complex, acting as facultative biotrophs in association with members of Apiaceae family, i.e., Ferula communis L. and Elaeoselinum asclepium L., respectively. The consumption of these fungi has rapidly increased in recent decades, not only thanks to their nutritional properties and pleasant flavor, but also for their bioactive and medicinal properties.MethodsA quantitative study of their hydroalcoholic extracts was carried out by liquid chromatography-mass spectrometry. The potential antimicrobial activity of the extracts was also tested against some phytopathogenic bacteria [Clavibacter michiganensis and Bacillus megaterium (Gram-positive), Pseudomonas viridiflava, Xanthomonas campestris, and Escherichia coli (Gram-negative)] and fungi (Aspergillus fumigatus, Penicillium italicum, Monilinia laxa, Botrytis cinerea, Cadophora sp., and Sclerotinia sclerotiorum).ResultsThe chemical analysis allowed the identification of secondary metabolites belonging to different classes, as flavonoids, organic acids, amino acids, carbohydrates, vitamins, nucleic acids, fatty acids, and triterpenoids. Both extracts demonstrated antimicrobial activity against of the most tested microorganisms.ConclusionThe results can broaden the knowledge on the possible use of these fungal species in the agricultural sector.